Bioactive Constituents of Shoot Extracts of Sisymbrium irio L. Against Fusarium oxysporum f. sp. cepae - AKHTAR,R. (2020)
ABSTRACT: The present study was carried out to check the antifungal potential of Sisymbrium irio L. shoot extract against Fusarium oxysporum f. sp. cepae (FOC). In preliminary bioassays, different concentrations (1 to 5%) of leaf, stem and fruit extracts were evaluated against FOC. All the extracts were effective against the pathogen. However, the leaf extract was found the most effective causing 25-41% decrease in FOC biomass. The fractionation of methanolic leaf extract was done by two organic solvents namely n-hexane and chloroform. Different concentrations (1.56 to 200 mg mL-1) of these fractions were tested against FOC. The n-hexane and chloroform fractions showed inhibitory activity against the pathogen and resulted in 77-93% and 80-96% reduction in biomass of FOC, respectively. GC-MS analysis showed the presence of 24 compounds in n-hexane and 4 compounds in chloroform fraction. In n-hexane fraction, β-sitosterol (18.64%) was the most abundant compound followed by orotic acid, bis(tert-butyldimethylsilyl)-, tert-butyldimethylsilyl ester (12.18%), 10-octadecenoic acid, methyl ester (7.90%) and 1,2-benzenedicarboxylic acid, diisooctyl ester (6.05%). Major compounds identified in chloroform fraction were 1,3-benzenedicarboxylic acid, bis(2-ethylhexyl) ester (50.82%) and di-n-octyl phthalate (33.00%). This study concludes that n-hexane and chloroform fractions of methanolic leaf extract of S. irio contain potent antifungal constituents for the management of FOC.